Implementasi Green Lean Six Sigma Pada Industri Manufaktur Atap Fiber Semen untuk Perbaikan Gain Yield dengan Analisis Biaya (Studi Kasus PT. X Kab. Bekasi) - Muhammad Riza Saifurrizqi Azizi; Tjandra, Sugih Sudharma (Jurnal Rekayasa Sistem Industri, 2026)
PT X is a manufacturing industry that produces fiber cement roofing. In company's business organization and operations, there is a KPI called LCP which one of the parameters is gain yield. Gain yield for the period January until December 2022 is in the range of 20.1% up to 30.4% with the target in the LCP which is 28% up to 34%. In the fiber cement roof production process generated waste, waste from the process is recycled and the processing results are called recycle slurry (RS) for reuse in the process. The research was conducted on production line 7 with the DMAIC method, Value Stream Mapping (VSM), and cost analysis to increase yield gain. The initial measurement of the average yield gain was 27.30% and the CTQ parameter capability process (CpK) did not meet the requirements with CpK value less than 1.33 and sigma level less than 4. The result of the improvement obtained gain yield of production line 7 increased to 29.46%. For the CpK value, the thickness of autoside sheet and the thickness of finish goods product increased to 1.01 and 1.00. CpK %use of recycle slurry, volumetry overflow, and volumetry loss vat increased to 1.34 up to 2.26. Sigma level of CTQ parameters after improvement is increased. Sigma level of autoside sheet thickness and thickness of finish goods products to 3.03 and 3.00. Sigma level %use of recycle slurry, volumetry overflow, and volumetry loss vat to greater than 4 sigma level. Implementation of Green Lean Six Sigma obtained savings in the use of raw materials and raw material costs, where an observation was obtained of Rp.1,249,512,253 per year or Rp. 104,126,021 per month.